2018
DOI: 10.1002/adhm.201701460
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles in Radiotherapy and Recent Progress in Nanobrachytherapy

Abstract: Over the last few decades, gold nanoparticles (GNPs) have emerged as "radiosensitizers" in oncology. Radiosensitizers are additives that can enhance the effects of radiation on biological tissues treated with radiotherapy. The interaction of photons with GNPs leads to the emission of low-energy and short-range secondary electrons, which in turn increase the dose deposited in tissues. In this context, GNPs are the subject of intensive theoretical and experimental studies aiming at optimizing the parameters lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 214 publications
0
117
0
2
Order By: Relevance
“…For experimental tumor models, female SCID mice (8-week-old) were inoculated with 1 × 10 7 U-87 MG glioblastoma cells into the right front leg in 100 µL fetal bovine serum free medium. Biodistribution studies were initiated approximately 12 days after cancer cell inoculation, when the tumors had reached a volume of 200-400 mm 3 . Tumor-bearing mice were randomly separated into two groups (n = 3-5 mice/time-point/group).…”
Section: Ex Vivo Biodistribution Studies Of [ 225 Ac] 225 Ac-au@tadotagamentioning
confidence: 99%
See 2 more Smart Citations
“…For experimental tumor models, female SCID mice (8-week-old) were inoculated with 1 × 10 7 U-87 MG glioblastoma cells into the right front leg in 100 µL fetal bovine serum free medium. Biodistribution studies were initiated approximately 12 days after cancer cell inoculation, when the tumors had reached a volume of 200-400 mm 3 . Tumor-bearing mice were randomly separated into two groups (n = 3-5 mice/time-point/group).…”
Section: Ex Vivo Biodistribution Studies Of [ 225 Ac] 225 Ac-au@tadotagamentioning
confidence: 99%
“…Therapeutic efficacy studies were performed in SCID mice bearing subcutaneous U-87 MG tumor xenografts when the tumor reached a volume of about 300 mm 3 (about 12 days after inoculation of glioma cells). Mice were randomly divided into two groups (n = 5 mice per group) and received three intratumoral injections of either normal saline (control group, 100 µL saline) or [ 225 Ac] 225 Ac-Au@TADOTAGA (therapy group, 100 µL NPs/ 5 kBq) (days of injection designated as Day 1, Day 3 and Day 5).…”
Section: Therapeutic Efficacy Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Most studies have focused on gold (Z = 79) nanoparticles and signi cant evidences have been reported to demonstrate their ability to increase the therapeutic ratio of radiotherapy. [16][17][18][19] Hafnium oxide (Z = 72) developed by NanoBiotix (France), has already shown success in the clinic as e cient radiation enhancers on patients requiring preoperative radiotherapy. [20] Other metal nanoparticles that have shown great promise in augmenting radiotherapy include bismuth (Z = 83) [21]; platinum (Z = 78) [22,23] and iron oxide [24,25] having both radiosensitizing and hyperthermic [26] properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is rational to find out a combination therapy with more precise technique to maximize the efficacy of the therapy and to overcome multidrug resistance in cancers. NP conjugation with chemotherapeutic drugs or using NPs during radiotherapy of cancer showed some promising outcome, with many of them approved for treatment of different cancer types [17]. The formulations of chemothera-peutical agents into nanoparticle have several advantages over the standard chemotherapy dosage form.…”
Section: Introductionmentioning
confidence: 99%